PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH DAN KOMUNIKASI MATEMATIS SISWA SEKOLAH MENENGAH PERTAMA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE (TPS) - Husna . (Jurnal Peluang, 2012)
AbstractProblem solving skills and communication skills is one of the mathematical achievement of the curriculum that must be owned by students in learning mathematics. For that, it needs the right learning model in improving communication skills and mathematical problem solving of students, one model that can improve this ability is a cooperative model of Think-Pair-Share. The aim of this research is to examine differences in mathematical problem solving skills and communication skills among students who obtain mathematical models of cooperative learning Think-Pair-Share and students who receive conventional learning. This research is an experimental study with the study design pre-test post-test control group design. With a population of all eighth grade students of MTsN Darul Ulum Banda Aceh by taking samples of the two classes of experimental class and control class through purposive sampling of four parallel classes available. The data was collected using a test instrument that tests problem solving skills and test students' mathematical communication skills. To see the difference in the ability of students between classes and grade control experiment used the t-test at significance level 0.05. Of the data and results of statistical tests were analyzed with SPSS 16.0 For Windows and Microsoft Excel 2007 to interpret the mathematical problem solving skills and communication skills of the students' mathematical model of cooperative learning with Think-Pair-Share, Overall cooperative models use Think - Pair - Share can improve mathematical problem solving and mathematical communication skills of students.     Keywords: Cooperative learning Think-Pair - Share, mathematical problem solving , mathematical communication